PERDAGANGAN ILEGAL TRENGGILING: EVALUASI DAN REKOMENDASI ATAS IMPLEMENTASI CITES DI INDONESIA - Parardhya Amara Putri Puntarangi (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This article aims to assess the legal protection of pangolins from illegal trade in Indonesia in accordance with CITES, by analyzing the causes of CITES’ ineffectiveness in protecting pangolins, and how Indonesia could give pangolins a better protection from illegal trade. This article applies the method of prescriptive normative, with statute and conceptual approaches. This article focuses on finding the most fitting resolution for problems arising from the illegal trade of pangolins. The legal data provided in this article contains both primary and secondary data. The primary data being international treaties which under the present case is CITES, customary and general principles of international law. Secondary data includes textbooks, guidelines, and any sources that might show relevance along the research process.  This paper is also library-based, including the use of digital library. Data collection begins with the research approach and the gathered information will be analyzed. The results of this research show that there are multiple causes that could lead to CITES ineffectiveness in giving legal protection towards pangolins from illegal trade in Indonesia, along with a few changes needed to accommodate the main purposes of the treaty.